Empowering Prospective Indonesian Migrant Workers (CPMI) through the Productive Migrant Village Program (Desmigratif) - Afandi Sitamala (Probono and Community Service Journal, 2023)
The regulations concerning the protection of Indonesian migrant workers are outlined in Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers (PMI). According to Article 7, the protection of prospective migrant workers must be provided in three stages: pre-employment protection, protection during employment, and post-employment protection. It is the responsibility of the state to ensure the provision of these protections. To facilitate services for prospective Indonesian Migrant Workers (CPMI) during the pre-departure stage, as well as for returned migrant workers and their families, the Ministry of Manpower initiated the establishment of Productive Migrant Villages (Desmigratif). Lempuyang Village, located in the Tanara District of Serang Regency, Banten Province, is one of the significant PMI-sending villages and is also among the targeted "Desa Binaan" villages of Untirta. This community service program adopts a community education approach through counseling sessions aimed at enhancing the understanding of Desmigratif. Additionally, training sessions are provided to CPMI in Lempuyang Village.